The Effect of Providing Digital Education Through Smartphone Applications on Control Level of Asthma Patients at Outpatient Clinic University of North Sumatra Hospital Medan - Pohan, Indah Triana Sari; Tarigan, Amira Permatasari; Pandiaman, Pandia; Erna, Mutiara (Journal of Society Medicine, 2025)
Introduction: Asthma is a chronic airway disease where achieving and maintaining asthma control is the main goal of management. Effective asthma control requires good patient self-management, including the ability to recognize symptoms and take appropriate action. This study aimed to assess the effect of digital education through the Paru Sehat smartphone application on asthma control levels in patients at the Outpatient Clinic of the University of North Sumatra Hospital, Medan. Method:This study used a quasi-experimental within-subject (pre-post) design. Asthma control levels were measured using the Asthma Control Test (ACT) before and after the use of the Paru Sehat application. Data analysis was conducted using a paired t-test for normally distributed data and the Wilcoxon test for non-normal data. A p-value <0.05 was considered statistically significant. Results: Before the intervention, 56% of patients had partially controlled asthma, 40% were uncontrolled, and only 4% were fully controlled. After using the Paru Sehat application, the proportion of fully controlled patients increased to 20%, partially controlled decreased to 48%, and uncontrolled cases reduced to 32%. However, this improvement was not statistically significant (p = 0.058). Conclusion: The use of the Paru Sehat application showed a trend toward improved asthma control, but the change was not statistically significant. Further research with a larger sample size and longer intervention duration may be needed to determine its effectiveness.